Rotor Aerodynamic Interference Of Aerial-Aquatic Vehicles In Free Water Surface Effect - Zhan, Q.; Yang, Y.; Zhao, S.; Xu, Y.; Wang, X.; Hu, J. (My University, 2025)
In recent years, aerial-aquatic rotorcraft that operate across multiple mediums have attracted considerable attention from researchers due to their unique flight capabilities. However, when rotorcraft traverse different media or operate near the water surface, they are required to overcome aerodynamic interference caused by the complex gas-liquid multiphase flow field. This reduces the confidence of aerodynamic performance evaluation models used in the design process, as well as the robustness of control systems designed based on these aerodynamic models, leading to failures in vehicle traversal or decreased hovering stability. In this study, the Lattice-Boltzmann method and turbulence model based large-eddy simulation method were employed to investigate the aerodynamic interference characteristics of isolated rotors and parallel multi-rotors near the water surface. Subsequently, a near-water surface/ground experimental system was established to compare and validate the effectiveness and computational accuracy of the numerical simulation models. The study found that the depression region caused by the deformation of the water surface obstructs the diffusion of the rotor wake, leading the isolated rotor to temporarily enter a vortex ring state, resulting in aerodynamic losses. Compared to the traditional ground effect, the thrust enhancement effect of the wall effect under the influence of gas-liquid coupling is suppressed, and may even be lower than the thrust without ground effect. Unlike isolated rotors, the thrust reduction caused by the free-water surface effect can be effectively mitigated by controlling the inter-rotor spacing of parallel multi-rotors. However, the cost of this mitigation is that the gas-liquid coupling effects increase the disorder in the flow field, exacerbating the imbalance in the aerodynamic force distribution across the rotor plane.